A randomised comparison of cognitive behavioural therapy (CBT) and eye movement desensitisation and reprocessing (EMDR) in disaster-exposed children - de Roos, Carlijn (Co-Action Publishing, 2011)
BACKGROUND: Building on previous research with disaster-exposed children and adolescents, a randomised clinical trial was performed in the treatment of trauma-related symptoms. In the current study two active treatments were compared among children in a broad age range and from a wide diversity of ethnic populations. OBJECTIVE: The primary aim was to compare the effectiveness and efficiency of Cognitive Behavioural Therapy (CBT) and Eye Movement Desensitisation and Reprocessing (EMDR). DESIGN: Children (n=52, aged 4–18) were randomly allocated to either CBT (n=26) or EMDR (n=26) in a disaster mental health after-care setting after an explosion of a fireworks factory. All children received up to four individual treatment sessions over a 4–8 week period along with up to four sessions of parent guidance. Blind assessment took place pre- and post-treatment and at 3 months follow-up on a variety of parent-rated and self-report measures of post-traumatic stress disorder symptomatology, depression, anxiety, and behaviour problems. Analyses of variance (general linear model repeated measures) were conducted on the intention-to-treat sample and the completers. RESULTS: Both treatment approaches produced significant reductions on all measures and results were maintained at follow-up. Treatment gains of EMDR were reached in fewer sessions. CONCLUSION: Standardised CBT and EMDR interventions can significantly improve functioning of disaster-exposed children.